2022
DOI: 10.3390/children9020186
|View full text |Cite
|
Sign up to set email alerts
|

Totally Excited about Moving Mobility and Exercise (TEAM Me): A Successful Multidisciplinary Exercise Quality Improvement Initiative for Pediatric and Young Adult Oncology and Stem Cell Transplant Inpatients

Abstract: Background: Pediatric, adolescent and young adult (PAYA) patients are less active than their healthy counterparts, particularly during inpatient stays. Methods: We conducted a quality improvement initiative to increase activity levels in patients admitted to our pediatric oncology and cellular therapy unit using a Plan-Do-Study-Act (PDSA) model. An interdisciplinary team was assembled to develop an incentive-based inpatient exercise and activity program titled Totally Excited About Moving Mobility and Exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The acute care setting accounted for the largest number of included studies ( n = 41, 59%), 27,28,33,34,37,39-42,45,46,48,50,52,53,55,58,59,62,66,68,70-74,76-78,88,89,95-98,100-105 followed by the outpatient setting ( n = 19, 27%). 29-32,36,38,47,49,54,56,60,61,64,67,69,79,80,93,99 Other practice settings included inpatient rehabilitation ( n = 6, 8.6%), 36,43,57,65,75,76 home health ( n = 2, 2.9%), 44,63 other ( n = 2, 2.9%), 19,81 and academia ( n = 2, 2.9%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The acute care setting accounted for the largest number of included studies ( n = 41, 59%), 27,28,33,34,37,39-42,45,46,48,50,52,53,55,58,59,62,66,68,70-74,76-78,88,89,95-98,100-105 followed by the outpatient setting ( n = 19, 27%). 29-32,36,38,47,49,54,56,60,61,64,67,69,79,80,93,99 Other practice settings included inpatient rehabilitation ( n = 6, 8.6%), 36,43,57,65,75,76 home health ( n = 2, 2.9%), 44,63 other ( n = 2, 2.9%), 19,81 and academia ( n = 2, 2.9%).…”
Section: Resultsmentioning
confidence: 99%
“…There were six unique study designs applied to QI publications, of which 34 studies (49%) 28,32-34,36,37,39,41,42,45-48,50-53,55,58,59,67,68,70,72,74,77,95-102 used a pre-post design. The second most commonly used design was an adaptive-iterative design ( n = 17, 24%) 29,30,35,38,54,56,57,61,63-66,73,75,78,80,93 in which studies reported using multiple cycles of improvement that were informed and adapted based on initial successes or failures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise has been shown to be effective in ameliorating mental health–related issues such as depression [ 5 , 6 ] and dementia [ 7 , 8 ]. Despite the significant effectiveness of exercise as a complementary method to improve the symptoms of mental health issues, it is challenging for people to remain engaged in and motivated to continue exercising [ 9 , 10 ]. Therefore, it is vital to provide users with physical activity–based immersive and fun interventions to optimize retention.…”
Section: Introductionmentioning
confidence: 99%